Performance Participation of Peucicap in West Aceh - Tausya, Resi Syahrani; Lubis, Tasnim (TALENTA Publisher, 2023)
This study aims to describe the performance and participation in the traditional Peucicap ceremony in Gunong Panah Village, Bubon District, West Aceh District. This study uses a descriptive qualitative method with an ethnographic approach. The results showed that in the Peucicap process, participation performance was seen in the act of giving advice, giving names, giving honey to the child (cicap), giving teungku needs related to the procession, and asking about the next procession. The participation of the family or parents of the baby is seen through the act of answering questions and asking questions. This research makes an important contribution to understanding, preserving culture, and developing methods in efforts to preserve and promote the Peucicap tradition and local culture in Aceh.